A rapid echocardiographic screening protocol for rheumatic heart disease in Samoa: a high prevalence of advanced disease. (15th June 2017) - Allen, Marvin; Allen, John; Naseri, Take; Gardner, Rebecca; Tolley, Dennis; Allen, Lori
Abstract: Background: Echocardiography has been proposed as a method to screen children for rheumatic heart disease. The World Heart Federation has established guidelines for echocardiographic screening. In this study, we describe a rapid echocardiogram screening protocol according to the World Heart Federation guidelines in Samoa, endemic for rheumatic heart disease. Methods: We performed echocardiogram screening in schoolchildren in Samoa between 2013 and 2015. A brief screening echocardiogram was performed on all students. Children with predefined criteria suspicious for rheumatic hear diseases were referred for a more comprehensive echocardiogram. Complete echocardiograms were classified according to the World Heart Federation guidelines and severity of valve disease. Results: Echocardiographic screening was performed on 11, 434 children, with a mean age of 10.2 years; 51% of them were females. A total of 558 (4.8%) children underwent comprehensive echocardiography, including 49 students who were randomly selected as controls. Definite rheumatic heart disease was observed in 115 students (10.0 per 1000): 92 students were classified as borderline (8.0 per 1000) and 23 with CHD. Advanced disease was identified in 50 students (4.4 per 1000): 15 with severe mitral regurgitation, five with severe aortic regurgitation, 11 with mitral stenoses, and 19 with mitral and aortic valve disease. Conclusions: We successfully applied a rapid echocardiographic screening protocol to a large number of students over a short time period – 28 days of screening over a 3-year time period – to identify a high prevalence of rheumatic heart disease. We also reported a significantly higher rate of advanced disease compared with previously published echocardiographic screening programmes.